Chemistry and Functionality of Bioactive Compounds Present in Persimmon. (23rd February 2016) - Yaqub, Shazia; Farooq, Umar; Shafi, Afshan; Akram, Kashif; Murtaza, Mian Anjum; Kausar, Tusneem; Siddique, Farzana
Abstract : Extensive research has related the consumption of persimmon with the reduced risk of various diseases and particularly highlighted the presence of bioactive phenolic compounds for their therapeutic properties. Major phenolic compounds present in persimmon are ferulic acid, p -coumaric acid, and gallic acid. β -Cryptoxanthin, lycopene, β -carotene, zeaxanthin, and lutein are important carotenoids having antioxidant potential. They are important to prevent oxidation of low-density lipoproteins, safeguard beta cells of the pancreas, and reduce cardiovascular diseases, cancer, diabetes mellitus, and damage caused by chronic alcohol consumption. In this paper, the chemistry and health benefits of bioactive compounds present in persimmon are reviewed to encourage impending applications and to facilitate further research activities.